Intracranial infection due to otitis media with a tegmen defect: Surgical approach - Sousa Menezes, Ana (2019)
Objectives: To report the experience of our department in the surgical approach of the patients admitted between 2012 and 2018 for intracranial infection of otogenic etiology, in the context of a tegmen defect. Study Design: Retrospective, Case Series Material and Methods: Pre-existing otological pathology, intracranial complication, surgical approach and its timing, materials used to correct the defect, as well as the follow-up time were evaluated. Results: Twelve patients who underwent surgical treatment for intracranial infectious complications (meningitis / abscess / meningoencephalitis / septic venous thrombosis) were included. The most frequent etiology was cholesteatomatous chronic otitis media. The transmastoid approach was the most used. In two cases a combined approach with the collaboration of Neurosurgery was used. Only one case required revision surgery. Conclusion: The correction of the infectious focus is crucial for the resolution of intracranial complication, and its early multidisciplinary approach is important. The transmastoid approach is a safe, familiar and highly effective option for the otolaryngologist.